Posebnosti rehabilitacije po operativnem zdravljenju poškodb hrustanca v kolenskem sklepu - Bregar, Martina (Rehabilitacija (Ljubljana), 2009)
Treatment of focal cartilage defects is very difficult. The goal of the treatment is restitution of joint function and absence of symptoms, especially pain. The final results of treatment depends on the quality and safety of the rehabilitation procedure. Statistics on outcome after the presently standard rehabilitation after are encouraging. Even better results are expected in the future in the light of new knowledge regarding all aspects of this type of procedures. More precise rehabilitation protocols are to be expected.
Keywords: kolenski sklep; hrustanec; poškodbe; therapy; zdravljenje; vocational rehabilitation; rehabilitacija